Recombinant inbred lines derived from cultivars of pea for understanding the genetic basis of variation in breeders' traits. Issue 5 (29th November 2018) - Moreau, Carol; Knox, Maggie; Turner, Lynda; Rayner, Tracey; Thomas, Jane; Philpott, Haidee; Belcher, Steve; Fox, Keith; Ellis, Noel; Domoney, Claire
Abstract: In order to gain an understanding of the genetic basis of traits of interest to breeders, the pea varieties Brutus, Enigma and Kahuna were selected, based on measures of their phenotypic and genotypic differences, for the construction of recombinant inbred populations. Reciprocal crosses were carried out for each of the three pairs, and over 200 F2 seeds from each cross advanced to F13 . Bulked F7 seeds were used to generate F8 –F11 bulks, which were grown in triplicated plots within randomized field trials and used to collect phenotypic data, including seed weight and yield traits, over a number of growing seasons. Genetic maps were constructed from the F6 generation to support the analysis of qualitative and quantitative traits and have led to the identification of four major genetic loci involved in seed weight determination and at least one major locus responsible for variation in yield. Three of the seed weight loci, at least one of which has not been described previously, were associated with the marrowfat seed phenotype. For some of the loci identified, candidate genes have been identified. The F13 single seed descent lines are available as a germplasm resource for the legume and pulse crop communities.